SH2D5 promotes lung adenocarcinoma cell metastasis and triggers EMT via activating AKT signaling pathway. - Licheng Du; Wenjia Ren; Linjun Liu; Haojia Zhu; Ke Xu; Yubai Zhou (PLoS ONE)
Lung adenocarcinoma (LUAD) is the most common histological subtype of lung cancer, characterized by a high incidence in late stages, high mortality rate, and poor prognosis. Src Homology 2 Domain Containing Protein 5 (SH2D5) is a mammalian-specific, uncharacterized scaffolding protein, and its role in LUAD remains unclear. In the present study, we investigated the function and potential mechanisms of SH2D5 in the progression of LUAD. We found aberrant expression of SH2D5 in LUAD tissues and cells, and its high expression is closely associated with poor prognosis in LUAD patients. Through loss-of-function and gain-of-function experiments, we revealed that overexpression of SH2D5 promotes the proliferation and migration abilities of lung adenocarcinoma cells. Gene set enrichment analysis (GSEA) revealed that SH2D5 positively regulates the epithelial-mesenchymal transition (EMT) process in lung adenocarcinoma cells. Additionally, we found that regulating the expression of SH2D5 influenced the phosphorylation levels of AKT, and the rescue experiments with AKT pathway activators/inhibitors partially reversed the tumor progression and EMT processes induced by SH2D5. In summary, our study demonstrated that SH2D5 promotes the migration and EMT process of LUAD cells through the AKT signaling pathway, suggesting that SH2D5 may serve as a crucial potential target for the treatment of metastatic LUAD.